Of God and gods: Egypt, Israel, and the rise of monotheism - Assmann, Jan (George L. Mosse series in modern European cultural and intellectual history, 2008)
"An important contribution to the fields of Egyptology, Biblical studies, and the general study of religion." - Israel Knohl, Hebrew University, Jerusalem"